2017
DOI: 10.1037/neu0000350
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control and associated neural correlates in adults with spina bifida myelomeningocele.

Abstract: Objective Accelerated aging can occur in adult survivors of neurodevelopmental disorders, but has been narrowly studied in spina bifida myelomeningocele (SBM). Since discrete aspects of cognitive control and related neural network macrostructure deteriorate in normal aging, the specificity and trajectory of cognition and neuropathology incurred across adulthood in SBM were examined. Method Adults (N = 120) with and without SBM completed working memory span and manipulation tasks, and an inhibitory control ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…Although SB has a lower-case fatality rate than other neural tube defects, it often results in severe life-long disability and morbidity. Moreover, now that the oldest cohort with SB is nearly 60 years of age, a better understanding of age-related changes across the lifespan is critical to inform and improve clinical care for this population (Dennis, Spiegler, & Hetherington, 2000; Ware, Kulesz, Juranek, Cirino, & Fletcher, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although SB has a lower-case fatality rate than other neural tube defects, it often results in severe life-long disability and morbidity. Moreover, now that the oldest cohort with SB is nearly 60 years of age, a better understanding of age-related changes across the lifespan is critical to inform and improve clinical care for this population (Dennis, Spiegler, & Hetherington, 2000; Ware, Kulesz, Juranek, Cirino, & Fletcher, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Central province --1.2 MMC -myelomeningocele tool that allows early diagnosis during the first trimester. 1 Any treatment or management options undertaken during this period must be carried out with much caution, especially in our conservative Muslim culture. We looked at this issue from 2 perspectives, as based on the opinion of the Islamic Fiqh (Jurisprudence) council, under the umbrella of the Muslim world league.…”
Section: Studymentioning
confidence: 99%
“…Epilepsy and low intelligence quotient (IQ) are potential major neurological complications of MMC. 1,2 Moreover, neural tube defects necessitate rehabilitation and multiple subspecialty clinic visits, as well as potential surgeries for bowel, bladder, and leg deformities. This pathology results from a failure of the neural tube to close, which leads to spinal cord exposure, known as spina bifida (SB), of which MMC is the most common type.…”
mentioning
confidence: 99%
“…Furthermore, according to several studies many other individuals with SB show impaired executive functions (EF) 1 , which become more evident when performing more complex activities ( 5 ). Impaired working memory ( 9 ), a part of EF ( 8 ), and prospective memory ( 10 ) are also common, as well as attention disorders ( 11 ), impaired processing speed, timing deficits ( 5 ), problems with time management ( 12 ) and with getting things done ( 13 ). Impaired visuospatial function is also common ( 11 ).…”
mentioning
confidence: 99%
“…These cognitive impairments can be observed in childhood and become more evident during adolescence and adulthood, when activities of daily living (especially taking care of your own household), education, work and relations put increased demands on the person ( 14 ). Several studies found that cognitive impairments in individuals with SB do not decrease with maturity, but persist into adulthood ( 9 , 14 ). Furthermore, impairments in prospective memory have also been shown to increase for persons over 32 years of age ( 10 ).…”
mentioning
confidence: 99%